Pengaruh Penyaluran Dana ZIS, Inflasi, Dan Gini Ratio Terhadap Tingkat Kedalaman Kemiskinan Satu Dekade - Muhammad Fatchullah El Islami; Achmad Room Fitrianto (ITB AAS INDONESIA Surakarta, 2023)
The problem of poverty is still an important part of macroeconomic discussions. Indicators of the welfare of a country can be measured, one of which is by the variable poverty. The increase or decrease in poverty in Indonesia is an achievement in the world of economic development. Some assumptions suggest that this level of poverty cannot be eliminated as a whole. This study will answer the effect of ZIS, Inflation, and Gini Ratio fund disbursements on the Depth of Poverty in the last decade. This research uses a descriptive quantitative approach by using secondary data each semester derived from the publications of Badan Pusat Statistik (BPS), Bank Indonesia (BI), and Badan Amil Zakat Nasional (BAZNAS). The purpose of this study is to provide empirical evidence related to the Effect of ZIS Fund Disbursement, Inflation, and Gini Ratio on Poverty Depth Level. This study used a multiple linear regression analysis method. The results showed that ZIS and Inflation Fund Disbursements did not have a significant effect on the Poverty Depth Level. Meanwhile, the Gini ratio variable has a significant effect on the depth of poverty.